Cuscuta campestris Yunck.: An emerging threat to the indigenous flora of Assam, India - Das, Barnali; Nath, Namita (Ecological Questions, 2024)
Cuscuta campestris is a well-known holoparasitic angiosperm of the family Convolvulaceae. This leafless, rootless, achlorophyllous angiospermic parasite rapidly expands through its diverse host range. This species also shows self-parasitism. The study recorded 92 host species; Mikania micrantha and Christella dentata being the most preferred hosts. In this manuscript, the taxonomic description of C. campestris, its host range, the anatomy of infected host parts and the nature of parasitism are described. This parasite can bring great loss in sectors like agriculture or horticulture by affecting the economically important host plants. This invasive neophyte must be controlled as soon as possible.